Using readings beyond the textbook: A survey. Issue 4 (2nd October 2021) - Allgood, Sam; McGoldrick, KimMarie
Abstract: Incorporating readings beyond the textbook is one way to broaden economic content across all courses. While previous studies document the extent to which narrowly defined categories (press readings, scholarly articles) are used, none to date provide details as to how such readings are incorporated. This study was intended to document use in greater detail than previously published and identify example uses that were innovative.